Analysis Of The Addition Of Coca-Cola Sludge For Quality Compost Production - Arthagama, I Dewa Made; Dana, I Made (International Journal of Biosciences and Biotechnology, 2023)
Bali as a tourist destination makes a perfect location for the soft drink industry, Coca-Cola, to build their factory which is located in Mengwi District, Badung Regency, Bali, Indonesia. In the production process of the beverage industry, of course, it produces by-products in the form of solid waste sludge that is not utilized. This study aims to determine the compost formula with the addition of Coca-cola sludge to improve the quality of the compost. This research was conducted from June to July 2021, using a completely randomized design (CRD) consisting of 11 formulations of compost material, which was repeated 3 times so that 33 experiments were obtained. The results showed that the treatment G = (2.5 kg goat manure + 1.5 kg rice straw + 0.5 kg Coca-cola sludge) gave the best compost quality as indicated by the highest N, P, and K parameter values, the best C/N ratio, and pH approach to neutral.  It should be tried to be applied in the field for plant growth and production using several plants and in several types of soil